Democracy and Multiculturalism: Are Minorities´ rights compatible with Liberal Democracy´s principles? (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
After the fall of former Communist countries in Eastern Europe, and according to the analysis on its causes, debate on the political philosophy related to ethnic minorities in liberal democracies has been more intense. This essay deals with the subject matter from a liberal and communal perspective, focusing on the reflection about the following question: Are minorities´ rights compatible with Liberal Democracy´s principles?
Keywords: Liberalism; Communitarianism; Natioanl minorities; multiculturalness; State-Nation